Production and characterization of extracellular polymeric substances (EPS) generated by a carbofuran degrading strain Cupriavidus sp. ISTL7. (June 2019) - Gupta, Juhi; Rathour, Rashmi; Singh, Rashmi; Thakur, Indu Shekhar
Graphical abstract: Highlights: Cupriavidus sp. ISTL7 was found to be a mesophilic and acidophilic strain. ISTL7 was evaluated for carbofuran degradation. Utilization of carbofuran was 98% at 400 ppm with bacterial cell growth. Bacterial treatment of carbofuran leads to decline in its cytotoxicity in HepG2. EPS production with carbofuran was 3.112 ± 0.3682 g L −1 with no toxicity. Abstract: The present study demonstrates EPS production by Cupriavidus sp. ISTL7 along with its capability to remediate a toxic carbamate pesticide, carbofuran. The strain ISTL7 efficiently degraded approximately 98% of carbofuran (400 ppm) within 96 h. GC–MS analysis showed catabolic metabolites of degradation which included carbofuran-7-phenol, methylamine, 2-hydroxy-3-(3-methylpropan-2-ol)benzene- N -methyl-carbamate etc. EPS production from the mineral medium supplemented with carbofuran was observed to be 3.112 ± 0.3682 g L −1 . FTIR confirmed its carbohydrate composition and the monomeric sugars: glucose, xylose, sorbitol and fructose were identified by GC–MS analysis. The toxic potential of degradation experiment and the produced EPS was evaluated on HepG2 (mammalian liver cell line). The cytotoxicity of carbofuran was reduced upon bacterial degradation and the formed EPS was found to be non-toxic as inferred from percentage cell viability. The present research can possibly influence the development strategies of biological remediation.